'Carrots for Corporate Sustainability': Impacts of Incentive Inclusiveness and Variety on Environmental Performance. (26th May 2017) - Dahlmann, Frederik; Branicki, Layla; Brammer, Stephen
Abstract: In this paper we explore the role that managerial incentives play in improving corporate environmental performance, finding that greater inclusiveness of incentive beneficiaries and greater variety of incentive types are important factors in firms' incentive schemes. Drawing on a large dataset of multinational enterprises, our results suggest that including more beneficiaries from different levels within the corporate hierarchy and offering both monetary and non‐monetary rewards are generally more likely to lead to reductions in corporate greenhouse gas emissions. Developing two principles of incentive design, inclusiveness and variety, and the conceptualization of patterns of these in organizations as configurations of incentives, our research contributes substantially to normative advice regarding the relative effectiveness of alternative systems of environmental incentives. Such an understanding of the potential of incentives is critical to informing how firms address complex problems such as sustainability in the context of increasingly extended organizational hierarchies and designs. Copyright © 2017 John Wiley & Sons, Ltd and ERP Environment